Supporting Instructional Process with PowerPoint : Experience from Multimedia Technology Subject - Syahrul Nizam, Junaini; Jonathan, Sidi (Academic Quality Synposium, 2007)
Effective instructional support has a crucial impact on learning process especially on the students’ cognitive effect. In this case PowerPoint is a unique teaching tool that has been widely used on and off the campus. The advancement in software development has made electronic presentation using PowerPoint as the norm in the university setting. As a university lecturer, mastering how to prepare effective PowerPoint presentation contents has become crucial. This paper will examine the teaching and learning process from information architecture and visualization perspective. It discusses how to apply these theories to develop the PowerPoint presentations that effectively support the instructional process. The discussion focuses on the aspect of visual design, textual communication and multimedia design. This paper examines how to prepare a highly usable and student-centered PowerPoint slides. The case study part presents our experience in preparation and innovation of the slides for Multimedia Technology Subject since the last five years. Example slides highlighting important instructional tips and tricks of using PowerPoint will also be presented.